Maternal Obesity and Its Association with Breastfeeding duration and Initation of Complementary Feeding - Mehtäjärvi, Milla-Maria (My University, 2023)
Backround: Maternal overweight can affect the success of breastfeeding and lead to early start of complementary feeding, leading to elevated risk of childhood weight problems. The aim of the study was to examine the relation of maternal overweight and obesity status, including body fat percentage, presence of gestational diabetes mellitus and gestational weight gain on 1) duration of exclusive and total breastfeeding 2) on infant feeding, specifically on onset of complementary feeding. Methods: Overweight and obese women were recruited (n=439) at early pregnancy with self- reported pre-pregnancy BMI ≥ 25 kg/m2 and were followed with their infants up to 24 months. Gestational diabetes mellitus was diagnosed with an oral glucose tolerance test. Participants kept a diary about initiation, duration of breastfeeding and initiation of infant complementary feeding. Results: 2-class BMI categories showed that obese mothers breastfed shorter time exclusively and started formula feeding earlier then overweight mothers (P<0.05). Exclusive breastfeeding was also short in 4-class BMI categories and among GDM mothers (P<0.05). All categories breastfed shorter time then recommended (P<0.05). Also, Obese mothers started complementary feeding of their infants earlier than overweight mothers in both BMI-categories (P<0.05). Conclusions: The results indicate that the rising BMI, more precisely obesity lead to early breastfeeding ceasing, being relied on formula sooner and start of complementary feeding a head of recommendation. Also, GDM showed to be a similar risk as rising BMI was. In future healthcare workers should focus on these mothers by providing adequate guidance and support before, during and after pregnancy to prevent weight gain related problems. Keywords: Obesity, overweight, breastfeeding, complementary feeding, gestational diabetes